Effects of the Incorporation of Bioactive Particles on Physical Properties, Bioactivity and Penetration of Resin Enamel Infiltrant - Souza AF; Souza MT; Damasceno JE; Ferreira PVC; Alves de Cerqueira G; Baggio Aguiar FH; Marchi GM (Dove Medical Press, 2023)
Ana Ferreira Souza,1 Marina Trevelin Souza,2 Janaína Emanuela Damasceno,1 Paulo Vitor Campos Ferreira,3 Gabriela Alves de Cerqueira,1 Flávio Henrique Baggio Aguiar,1 Giselle Maria Marchi1 1Department of Restorative Dentistry, Piracicaba Dental School, Campinas State University - UNICAMP, Piracicaba, São Paulo, Brasil; 2Laboratory of Vitreous Materials, Department of Materials Engineering, Federal University of São Carlos, São Carlos, São Paulo, Brasil; 3Department of Restorative Dentistry, Dental Materials Division, Piracicaba Dental School, Campinas State University - UNICAMP, Piracicaba, São Paulo, BrasilCorrespondence: Ana Ferreira Souza, Department of Restorative Dentistry, Piracicaba Dental School, Campinas State University - UNICAMP, Avenida Limeira, 901, Piracicaba, São Paulo, Brasil, 13414-903, Tel +55 098 98191-4015, Fax +55 019 2106-5218, Email fsana.ufma@gmail.comPurpose: The resinous infiltrant lacks remineralizing activity. This research aimed to develop and evaluate bioactivity, physico-mechanical properties and penetration of resin infiltrants containing Biosilicate or nanohydroxyapatite.Methods: Experimental resin infiltrant (ERI; 75/25 wt.% TEGDMA/BisEMA) was divided among the groups Pure Experimental (PE); ERI + Biosilicate 5 or 10% (Bio5; Bio10), ERI + 10% nanohydroxyapatite (Hap10), and Icon (DMG, Germany). Bioactivity was analyzed by SEM, EDS and FT-IR/ATR after soaking in SBF. Degree of conversion (DC), sorption and solubility (SO; SOL), flexural strength, modulus of elasticity (FS; E-modulus), contact angle (CA) and penetration were characterized. Extent of penetration was analyzed by treating white spot lesions (WSL) in human dental enamel samples with the infiltrants and subsequently analyzing specimens by confocal laser scanning microscopy. Data from each test were submitted to ANOVA and Tukey's tests (p < 0.01).Results: SEM, EDS and FT-IR showed the formation of precipitates and increase in the rates of Ca and P in the groups with bioactive particles, after storage in SBF. Hap10 showed higher DC and CA values than all the other groups. Groups Bio5 and Bio10 showed CA values similar to those of Icon, higher SO and SOL values, and reduction in other properties. All infiltrants were capable of penetrating into the WSLs.Conclusion: The incorporation of Biosilicate (5 or 10%) or nanohydroxyapatite (10%) into ERI induced mineral deposition on the surface and did not compromise infiltration and penetration into WSLs, however, compromising their physico-mechanical properties.Keywords: dental caries, dental enamel, hydroxyapatite, scanning electron microscopy, confocal laser scanning microscopy